2018
DOI: 10.1039/c8ce00269j
|View full text |Cite
|
Sign up to set email alerts
|

Bulky substituent and solvent-induced alternative nodes for layered Cd–isophthalate/acylhydrazone frameworks

Abstract: A series of three layered cadmium–organic frameworks containing acylhydrazone and (un)substituted isophthalates have been prepared and characterised.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 49 publications
1
8
1
Order By: Relevance
“…Further progress in gas-related technology could result from flexible MOFs, which are a subgroup of metal–organic frameworks that respond to external stimuli like adsorbates with considerable structural transformation. Intrinsic flexibility improves selectivity, considerably increases the working capacity, , enables self-accelerating CO sorption, and influences gas separation . However, examination of the transition mechanism caused by the external stimulus requires sophisticated in situ techniques, e.g ., nuclear magnetic resonance (NMR), powder X-ray diffraction (PXRD), infrared spectroscopy (IR), and others . The obtained information serves as input for the understanding–tuning–developing cycle for adjusting the crucial features of the adsorbent for advanced applications.…”
Section: Introductionmentioning
confidence: 99%
“…Further progress in gas-related technology could result from flexible MOFs, which are a subgroup of metal–organic frameworks that respond to external stimuli like adsorbates with considerable structural transformation. Intrinsic flexibility improves selectivity, considerably increases the working capacity, , enables self-accelerating CO sorption, and influences gas separation . However, examination of the transition mechanism caused by the external stimulus requires sophisticated in situ techniques, e.g ., nuclear magnetic resonance (NMR), powder X-ray diffraction (PXRD), infrared spectroscopy (IR), and others . The obtained information serves as input for the understanding–tuning–developing cycle for adjusting the crucial features of the adsorbent for advanced applications.…”
Section: Introductionmentioning
confidence: 99%
“…616 Another linear 1D chain is [Cd(tBu-iso)(pich)(DMF)]•2DMF (tBu-iso = 5-tert-butylisophthalate; pcih = 4-pyridinecarboxaldehyde isonicotinoyl hydrazine) in which adjacent chains in ABAB sequence undergo interdigitation via DMF molecules linked to metal centers. 617 Further similar 1D zigzag chains involved in interdigitation exhibit [2 + 2] cycloaddition photochemical reaction (see section 4). 618 Also, 1D ladder-like chains have been illustrated to exhibit interdigitation.…”
Section: Interdigitationmentioning
confidence: 99%
“…621 Similar relevant examples which involve interdigitation of 1D ladder polymers to 2D structures are [Cd 2 (tBu-ip) 2 (pcih) 2 ] and [Cd 2 (ip) 2 (pcih) 2 ], with adjoining ladders arranged in an ABAB manner. 617 Other than these, an example of 1D meso-helical nanotubular or step-ladder like polymer, [Cd 2 (ADC) 2 (bpp) 3 (H 2 O)] 2 • 8H 2 O (ADC = 1,3-adamantanedicarboxylic acid), displaying 1D to 2D interdigitated architecture with bpp as side arms (Figure 109). 622 Similarly, [Zn(L1)(bpee)] (L1 = H 2 L1 = 5-(benzyloxy)isophthalic acid) with open-ended tubular 1D structure exhibits 2D interdigitated framework controlled by hydrogen bond interactions.…”
Section: Interdigitationmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the different kinds of N‐containing linkers, bipyridine and their derivatives are widely employed in the construction of versatile MOFs with promising properties . In addition, it has been reported that some MOFs were constructed from rigid dicarboxylate and functionalized bipyridine by the mixed‐ligand strategy, which have intriguing structures and excellent properties . 2,5‐Bis(4‐pyridyl)thiazolo[5,4‐ d ]thiazole (Py 2 TTz) with rigid π‐conjugated system has good luminescence property , .…”
Section: Introductionmentioning
confidence: 99%